The physiological effect of zinc oxide (ZnO) nanopesticide on Aedes aegypti Larvae - Ting, Chuan Hsieh; Syahirah Zakaria,; Siti Khadijah Mohd Bakhori,; Shahrom Mahmud,; Siti Nasuha Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Aedes aegypti is responsible for transmitting various mosquito-borne diseases. Recently, there have been concerns about the negative impacts of the insecticides used in vector control including insecticide resistance development in the mosquito population. These circumstances lead to efforts to develop other strategies for controlling mosquito vectors. As technology in nanoparticles advances, zinc oxide (ZnO) nanoparticles have the potential as the alternative for chemical pesticides for mosquito larvicides due to their optical properties and widespread usage in different industries. The purpose of this study was to determine the toxicity of ZnO nanoparticles towards Ae. aegypti larvae and to examine the physiologies of Ae. aegypti mosquito larvae treated with ZnO nanoparticles at LC50 level. Toxicity bioassays were carried out to determine LC50 and LC90 values. The larvae surface and midgut treated with LC50 ZnO were examined using the Scanning Electron Microscope (FESEM) and Dispersive X-ray spectroscopy (EDX). The LC50 and LC90 concentrations of ZnO nanoparticles after 4 hr of direct UV exposure against Ae. aegypti larvae were 49.141 mg/L and 64.195 mg/L, respectively. After exposure to ZnO nanoparticles, Ae. aegypti larvae showed morphological abnormalities, including distorted and shrunk body parts as well as midgut rupture. Overall, the findings suggest that ZnO nanoparticles have the potential to replace chemical pesticides as a means of reducing the populations of Ae. aegypti mosquitoes.